Modelling and simulation of battery electric vehicle with consideration of propulsion load and auxiliary load - Tengku Mohd, Tengku Azman; Hassan, Mohd Khair; Aris, Ishak; Che Soh, Azura (2019)
As electric vehicle becomes a favorable alternative for sustainable and cleaner energy emission in transportation, modeling and simulation of electric vehicle has attracted increasing attentions to the researchers. The preliminary study of electric vehicle is preferably done using simulation software to avoid expensive on the road test and reducing manufacturing time. Therefore, it is important to ensure a comprehensive simulation model of the battery electric vehicle (BEV) considering both propulsion and auxiliary load in order to obtain accurate data analysis. This new and improved BEV simulation model was developed based on mathematical equation using white-box modelling in Matlab-Simulink environment. The model consists of BEV powertrain; HV and LV battery, DC-DC converter, DC-AC inverter/rectifier, transmission gearing, tire, vehicle dynamic, controller (driver), electrical motor (PMAC) as propulsion load and two groups of auxiliary loads. The simulation test in three driving cycles has verified its robustness and effectiveness in achieving the performance objectives.